Dementia risk in women higher in same‐sex than opposite‐sex twins - Luo, Jing (Alzheimers Dement (Amst), 2020)
INTRODUCTION: Hormones may be one possible mechanism underlying sex differences in dementia incidence. We examined whether presumed differential prenatal hormone milieu is related to dementia risk by comparing dementia rates in same‐ and opposite‐sex dizygotic twin pairs in male and female twins. METHODS: The sample comprised 43,254 individuals from dizygotic twin pairs aged 60 and older from the Swedish Twin Registry. Survival analyses were conducted separately for females and males. RESULTS: Female twins from opposite‐sex pairs had significantly lower dementia risk than female twins from same‐sex pairs, but the differences emerged only after age 70 (hazard ratio = 0.64, P = 0.004). Results were not explained by postnatal risk factors for dementia, and no interaction between twin type and apolipoprotein E (APOE) ε4 was found. Male twins from same‐sex versus opposite‐sex pairs did not differ significantly. DISCUSSION: The results suggest that relatively masculine prenatal hormone milieus correlate with lower dementia risk in females.